Penerapan Rendam Kaki Air Hangat dengan Garam dan Serai Pada Lansia Hipertensi di Desa Kaliwungu Kabupaten Semarang - Nur Aisyah; Ida Nur Imamah (DIAGNOSA: Jurnal Ilmu Kesehatan dan Keperawatan, 2023)
Background: Elderly is a condition where a person is 60 years old. Hypertension is a condition of a person who has mixture of salt and lemongrass that can facilitate blood circulation in the body. systolic blood pressure of 140 mmHg and diastolic 80 mmHg. Data from the Kaliwungu Health Center (2023) shows that the number of hypertensive elderly is 18 elderly people. Non-pharmacological therapy that can be done by soaking warm water feet with aObjective: to determine the effect of the application of foot soak therapy using warm water with salt and lemongrass on blood pressure in elderly people with hypertension in Kaliwungu Village, Semarang Regency. Method: this application uses a case study research design with prestest and post-test design. Samples were 2 elderly people who had 2nd degree hypertension. Results: the application of there was a decrease in blood pressure that was different between respondent 1 and respondent 2 after the application of warm water foot soak with salt and lemongrass for 3 consecutive days for 20 minutes. Both respondents were categorized as grade 2 hypertension decreased to normal-high based on the PDHI classification (2019). Conclusion: Application of warm water foot soak with a mixture of salt and lemongrass can lower blood pressure in elderly people with hypertension.